Underpotential Deposition of Copper Clusters on Sulfur and Nitrogen Co‐Doped Graphite Foam for the Oxygen Reduction Reaction. Issue 22 (21st November 2019) - Xu, Jingsong; Li, Rui; Zeng, Rongguang; Li, Yingru; Pan, Qifa; Zhong, Hang; Chen, Jun
Abstract: In this study, we successfully fabricated approximately 1 nm copper clusters on sulfur and nitrogen co‐doped graphite foam (SNGF) by using an electrodeposition method. The introduction of sulfur dopants enhances the metal‐support interaction and, thus, allows the application of the underpotential deposition (UPD) technique on graphite foam. Furthermore, the strong S−Cu binding leads to the preferential formation and firm anchoring of Cu nuclei on monodispersed S sites. The controllable growth of Cu nuclei into Cu clusters is achieved by controlling the deposition amount by adjusting the electrochemical parameters. As an example, the supported Cu clusters were utilized towards oxygen reduction reaction catalysis, exhibiting a high catalytic activity and a long‐term durability. Remarkably, this strategy is promising for developing a general method to prepare other metal clusters (e. g. Ag clusters). Abstract : Control freak : Copper clusters of approximately 1 nm are successfully prepared by using an underpotential deposition method with the assistance of sulfur dopants in a graphite foam substrate. The growth of the copper clusters is well controlled by optimizing the deposition potentials and time durations.